Komunikasi Keterikatan: Trauma Personal Dalam Hubungan Asmara - Livia Eka Sabilla; Nina Yuliana (STIKes Ibnu Sina Ajibarang, 2024)
Establishing a romantic relationship is a common thing and often happens in every human life, even from a relatively young age. However, with the development of the times, more and more stories about romantic relationships are one of the reasons that hinder the occurrence of romantic relationships such as a poor family environment or the failure of previous romantic relationships. The purpose of this study is to analyze women's struggles in dealing with trauma due to the process of communication of attachment that occurred previously. The researcher uses a qualitative method with a case study approach. The subjects used in this study were three women who felt a bad impact on a romantic relationship by using Answorth's attachment pattern. The data collection method uses interview, observation, and informant techniques. The results of the study showed an overview of the three subjects about how much the previous relationship affected the next relationship and how they did to overcome it.